How to Stay Cool: Early Acoustic and Thermal Experience Alters Individual Behavioural Thermoregulation in the Heat - Udino, Eve; Mariette, Mylene M. (Frontiers in Ecology and Evolution, 2022)
Climate change is pushing organisms closer to their physiological limits. Animals can reduce heat exposure – and the associated risks of lethal hyperthermia and dehydration – by retreating into thermal refuges. Refuge use nonetheless reduces foraging and reproductive activities, and thereby potentially fitness. Behavioural responses to heat thus define the selection pressures to which individuals are exposed. However, whether and why such behavioural responses vary between individuals remains largely unknown. Here, we tested whether early-life experience generates inter-individual differences in behavioural responses to heat at adulthood. In the arid-adapted zebra finch, parents incubating at high temperatures emit “heat-calls,” which adaptively alter offspring growth. We experimentally manipulated individual early life acoustic and thermal experience. At adulthood, across two summers, we then repeatedly recorded individual panting behaviour, microsite use, activity (N = 2,402 observations for 184 birds), and (for a small subset, N = 23 birds) body temperature, over a gradient of air temperatures (26–38°C), in outdoor aviaries. We found consistent inter-individual variation in behavioural thermoregulation, and show for the first time in endotherms that early-life experience contributes to such variation. Birds exposed prenatally to heat-calls started panting at lower temperatures than controls but panted less at high temperatures. It is possible that this corresponds to a heat-regulation strategy to improve water saving at high temperature extremes, and/or, allow maintaining high activity levels, since heat-call birds were also more active across the temperature gradient. In addition, microsite use varied with the interaction between early acoustic and thermal experiences, control-call birds from cooler nests using the cooler microsite more than their hot-nest counterparts, whereas the opposite pattern was observed in heat-call birds. Overall, our study demonstrates that a prenatal acoustic signal of heat alters how individuals adjust behaviourally to thermal challenges at adulthood. This suggests that there is scope for selection pressures to act differently across individuals, and potentially strengthen the long-term fitness impact of early-life effects.